Evaluation of Patients with Neonatal Thrombosis - Guzoglu, Nilufer; Albayrak, Meryem; Aliefendioglu, Didem (Springer India, 2023)
The aim of the study is to characterize acquired and genetic risk factors and to give an account of the hereditary thrombophilia panel in neonatal thrombosis. All newborns diagnosed with neonatal thrombosis in a level III NICU were included in this retrospective cohort study. A total of 1850 patients were admitted to the NICU during the 5-y period; and 11 patients were diagnosed with thrombosis (0.58%). The most common risk factors were central venous catheter placement, hypoxia and prematurity and related complications, and sepsis. Four patients were investigated regarding the inherited risk factors for thrombosis. In these 4 patients, homozygous A1298C alleles of MTHFR and heterozygous FXIIIV34L mutations; homozygous PAI-SERPINE1 and heterozygous MTHFRA1298C mutations; compound heterozygous mutations of MTHFRC677T and MTHFRA1298C; and compound heterozygous mutations of MTHFRC677T, MTHFRA1298C, and PAISERPINE1 were detected respectively. In conclusion, neonatal thrombosis is multifactorial; newborns with acquired risk factors may also have hereditary risk factors.Trial InformationClinicalTrials.govIdentifier: NCT05367466
Keywords: Newborn; Thrombosis; Inherited risk factors